Survival Modelling of Repeated Events Using the Example of Changes in the Place of Employment - Wioletta Grzenda (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
This paper concerns the issue of survival modelling in the case of repeated events. In the modelling of this type of events, attention should be paid to the existence of dependence among the analysed durations, as well as the occurrence of unobserved heterogeneity. One of the ways to include these aspects in the analysis is to use models with random effects. The primary objective of this paper is to present the application of such models to analyse changes in the place of employment. The duration of individual periods of employment for the surveyed employees was modelled. The approach used made it possible to identify factors influencing decisions on job changes, but also to assess the risk of occurrence of events such as termination of employment, and to examine the impact of unobserved heterogeneity on the results of the estimations.